Design of Interactive Waste Sorting Program Using Engine Construct 2 as Alternative Learning Media - Mohammad Ikhsan Saputro; Sukendar, Toni; Sumbaryadi, Achmad; Ishaq, Ahmad; Santoso, Rame (Universitas Mohammad Husni Thamrin, 2025)
Environmental issues at the global and national levels are becoming important issues in efforts to keep the earth better. Unsustainable waste management results in pollution, ecosystem damage, and climate change are ongoing environmental problems. In Indonesia, unmanaged waste disposal disrupts the ecosystem and pollutes the environment. Open burning of waste emits toxic gases that are harmful to public health. The accumulation of plastic waste that is harmful to the environment is caused by excessive use of plastic waste and the lack of an efficient recycling system. To solve this problem, a broad approach is needed that includes policy changes, infrastructure financing, community education, and encouraging recycling practices. The Interactive Waste Sorting Program is a web-based learning tool designed to help elementary school students understand the types of waste and how to manage it. With interactive features such as images, sounds, songs, and evaluations, this game encourages learning. Research shows that Interactive Program-based learning increases student interest. The use of this application is expected to support resource conservation education, increase environmental awareness, and change the way students manage waste. The development of this Interactive Program application uses the waterfall method, which consists of the stages of requirements, design, implementation, verification, and maintenance. As a result, this Interactive Program allows students to play independently and help teachers deliver lessons. Overall, the development of this learning media is expected to encourage further innovation in information and communication technology-based education.